2023
DOI: 10.3389/fpubh.2023.1053206
|View full text |Cite
|
Sign up to set email alerts
|

Implementing interventions to promote spectacle wearing among children with refractive errors: A systematic review and meta-analysis

Abstract: PurposeTo investigate the level of compliance of children with refractive errors who are provided free spectacles, and to identify the reasons for non-compliance.MethodsWe systematically searched the PubMed, EMBASE, CINAHL, Web of Science, and Cochrane Library databases from the time these databases were established to April 2022, including studies published in English. The search terms were “randomized controlled trial” [Publication Type] OR “randomized” [Title/Abstract], OR “placebo” [Title/Abstract]) AND ((… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The findings suggest that learners with visual impairments in schools for the deaf have a higher need for visual aids because they rely on optimal vision to function. Visual impairments may affect their academic performance, and providing them with spectacles significantly improves their vision, which can lead to better academic outcomes and quality of life (Kwarteng et al 2024 ; Wu, Feng & Zhang 2023 ). Schools need to prioritise vision screening and the provision of spectacles for learners with hearing impairment not only to improve vision but also to enhance their educational and learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The findings suggest that learners with visual impairments in schools for the deaf have a higher need for visual aids because they rely on optimal vision to function. Visual impairments may affect their academic performance, and providing them with spectacles significantly improves their vision, which can lead to better academic outcomes and quality of life (Kwarteng et al 2024 ; Wu, Feng & Zhang 2023 ). Schools need to prioritise vision screening and the provision of spectacles for learners with hearing impairment not only to improve vision but also to enhance their educational and learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis demonstrated that free spectacles have significant effect on compliance among children and concluded that the combination of providing free spectacles along with educational interventions can lead to high levels of compliance among the study participants. [ 12 ] However, studies on spectacle-wearing compliance in infants with refractive errors complicated by different eye diseases are lacking.…”
Section: Introductionmentioning
confidence: 99%